Activated Carbon Monolith Derived from Coconut Husk Fiber as Electrode Material for Supercapacitor Energy Storage. (October 2020) - Taer, Erman; Naipospos, Verdy Manoto; Taslim, Rika; Agustino,; Apriwandi,
Abstract: Biomass-derived porous activated carbon materials have been receiving considerable attention in energy-storage devices especially for supercapacitor due to abundant, renewable, sustainable, and cost-effective production. In this study, porous activated carbon material with monolithic form has been successfully prepared from coconut husk fiber through one-stage integrated pyrolysis and ZnCl2 impregnation. Different physical activation temperature is the main focus in this study including 750, 800, 850, and 900 °C. The reduction of monolith dimensions such as mass, diameter, thickness and density have been reviewed as physical properties. Furthermore, the supercapacitor cells were performed with cyclic voltammetry t 1 M H2 SO4 aqueous electrolyte at low scan rate of 1 mV s −1 . The supercapacitor device based on the CFM-800 samples exhibited highest specific capacitance of 216 F g −1 . This sample also performed a promising performance with an energy density of 30.00 Whkg −1 and a high power density of 108.57 Wkg −1 . These results demonstrate that the coconut husk fiberhas been a high potential to as raw material for porous activated carbon monolith through low cost, vehicle and short-time processing with high-performance supercapacitors energy storage.